Staatsrechtslehrer des 20. Jahrhunderts: Deutschland - Österreich - Schweiz - Häberle, Peter (De Gruyter eBook-Paket Rechtswissenschaften, 2014)
This compendium presents the most important 20th century scholars in the German-speaking world in the field of public law. The work provides both personal and professional portraits of key legal figures, whose biographies are vividly tied the ebb and flow of constitutional principles. Peter Häberle, Universität Bayreuth; Michael Kilian, Universität Halle-Wittenberg; Heinrich Amadeus Wolff, Europa-Universität Viadrina Frankfurt (Oder).